Observational Analysis of Point-of-Care Lactate Plus™ Meter in Preclinical Trauma Models - Catharina Gaeth; Jamila Duarte; Alvaro Rodriguez; Amber Powers; Randolph Stone (Diagnostics)
Background/Objectives: Blood lactate concentration is often used to assess systemic hypoperfusion, tissue hypoxia, and sepsis in trauma patients and serves as a prognostic indicator and marker of response to therapy. Point-of-care (POC) devices provide rapid lactate measurements with a single drop of blood. In this study, lactate values from whole blood, measured with two POC devices, Abbott i-STAT® and the Nova Biomedical Lactate (LA) Plus™ meter, are compared. Methods: An observational analysis of 760 blood samples from four preclinical trauma animal models was performed. Lactate was measured simultaneously with two POC devices (i-STAT® and the Lactate Plus™ meter). The evaluation in the form of a Bland–Altman diagram showed the agreement of the tests. Results: The Spearman correlation was 0.9180 (95% CI 0.9056 to 0.9288) for i-STAT® vs. the LA Plus™ meter. Both tests showed a significant increase in lactate after injury (p < 0.05). The i-STAT® showed a small bias compared to the LA Plus™ meter (−0.0227 ± 0.4542 with 95% limits of agreement from −0.09129 to 0.8675). The LA Plus™ meter showed slightly higher values overall (0.0227 mmol/L), but the i-STAT® showed higher results at lactate levels above 2.5 mmol/L. Conclusions: The observed similarity in performance between the two devices suggests that both are capable of reliably measuring lactate levels in a trauma situation. The LA Plus™ meter provides fast results with only one drop of blood. This study supports the prehospital use of POC devices.